Integrated Notification System for Smart Parking Security Using Bot Telegram - Mohammad Liyananta Septipalan; Ida Bagus Ketut Widiartha; Ariyan Zubaidi; Muhammad Taufik (Jurnal Penelitian Pendidikan IPA, 2024)
Notification system for smart parking system is very important for parking security. The purpose of this research is to create a system used in parking security in the technical faculty of mataram university. The method used in this research is the flow of making a notification system using a telegram bot, namely determining the notification using a telegram bot and then creating a telegram bot that will send notifications to security guards, after the bot has been created, then coding the notification system so that the notification can run according to existing rules. The results showed that the notification system made runs according to predetermined rules as seen from the success of sending notifications to the security guard group. The conclusion is that the use of this notification system is a solution to parking security problems. This notification system can provide accurate information to security officers regarding information on vehicle data mismatches and vehicle license plates so that vehicles in the parking area can be monitored.